2018
DOI: 10.1111/jbg.12329
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational epigenetic variance for body weight in meat quails

Abstract: We aimed to estimate transgenerational epigenetic variance for body weight using genealogical and phenotypic information in meat quails. Animals were individually weighted from 1 week after hatching, with weight records at 7, 14, 21, 28, 35 and 42 days of age (BW7, BW14, BW21, BW28, BW35 and BW42, respectively). Single-trait genetic analyses were performed using mixed models with random epigenetic effects. Variance components were estimated by the restricted maximum likelihood method. A grid search for values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…This objective can be only achieved by considering additional information in the model such as measurements of the shared microbiota, methylation patterns reflecting epigenetic transmission, etc. Indeed, disentangling genetic and non‐genetic effects is challenging without additional information than pedigree and phenotypes (David & Ricard, 2019), which may explain the relatively low number of reports of significant epigenetic variance in the literature (Paiva, De Resende, Resende, De Oliveira, et al, 2018; Paiva, De Resende, Resende, Oliveira, et al, 2018; Varona et al., 2015). It has been proven by simulation that, in simple situations, the LRT comparing the animal and the transmissibility model is conservative (David & Ricard, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This objective can be only achieved by considering additional information in the model such as measurements of the shared microbiota, methylation patterns reflecting epigenetic transmission, etc. Indeed, disentangling genetic and non‐genetic effects is challenging without additional information than pedigree and phenotypes (David & Ricard, 2019), which may explain the relatively low number of reports of significant epigenetic variance in the literature (Paiva, De Resende, Resende, De Oliveira, et al, 2018; Paiva, De Resende, Resende, Oliveira, et al, 2018; Varona et al., 2015). It has been proven by simulation that, in simple situations, the LRT comparing the animal and the transmissibility model is conservative (David & Ricard, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the quantification of nongenetic inheritance for traits under selection is rare. Paiva et al (2018a) reported an epigenetic heritability of 0.10 for body weight in meat quails, while Difford et al (2018) estimated simultaneously that significant parts of the variance for CH4 emission in cattle were explained by genetics and the microbiota (0.21 and 0.13, respectively). To our knowledge, the part of variance explained by culture/behavioral inheritance has never been reported in the literature for livestock species.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our model combines the different sources of inheritance into a single transmissible value. However, the OWN Fortran program we propose to run the transmissibility model allows the different sources of inheritance to be separated if required, especially genetic and epigenetic inheritance, as described by Varona et al (2015) or Paiva et al (2018a,b). Furthermore, unlike previous methods proposed, the program that we propose has the advantage of (1) using a frequentist method for the estimations (faster than the Bayesian approach), (2) estimating the path coefficients (conversely to the grid search proposed by Paiva et al 2018a), and (3) allowing for different path coefficients for sires and dams, which has never been proposed before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos fenômenos epigenéticos em animais já foram reportados na literatura (Berghof et al 2013;Feeney et al 2014;Frésard et al 2013;Gao et al 2017;Leurox et al 2017;Li et al 2016;Triantaphyllopoulos et al 2016) demonstrando a necessidade de compreender plenamente a importância da epigenética na variabilidade fenotípica das características de importância econômica Poucos trabalhos procuram investigar e quantificar a variância epigenética transgeracional de características utilizadas como critérios de seleção nos programas de melhoramento. Alguns autores vêm propondo modelos estatísticos, incluindo herança epigenética e interações ambientais (Lopes et al 2015;Johannes & Colomé-Tatché 2011;Paiva et al 2018a;Paiva et al 2018b;Tal et al 2010;Varona et al 2015), oferecendo novos caminhos para uma futura inclusão destes mecanismos em estudos de seleção genética. A reversibilidade das modificações epigenéticas, ou seja, a sua natureza potencialmente transitória, poderia constituir um desafio na modelagem de herança.…”
Section: Metilação Do Dnaunclassified